Stakeholders and Corporate Social Responsibility (CSR) programme as key sustainable development strategies to promote corporate reputation: Evidence from Vietnam - Mai Ngoc Khuong; Nguyen Khoa Truong An; Tran Thi Thanh Hang (Cogent Business & Management, 2021)
The aim of this study is to analyse the relationship between stakeholder influence, CSR types and corporate reputation. CSR types in this research are economic, legal, ethical, environmental and philanthropic responsibility. Data were collected from surveys of 869 leaders and managers in the public, private and foreign direct investment (FDI) sectors. The research data were analysed using a partial least square-structural equation modelling (PLS-SEM) model incorporating measurement-model results (verifying internal consistency, reliability, convergent validity and discriminant validity) and structural model results (identifying the causal relationship among variables and confirming the research hypotheses). The results revealed that the stakeholder influence does not only significantly affect the CSR types but also positively affects corporate reputation. Further, CSR performance in legal, ethical, environmental, philanthropic responsibility except economic responsibility have a significant influence on corporate reputation. Based on the findings, the study considers CSR performance a valuable management tool for enhancing corporate reputation. It has implications for the improvement of CSR management and sustainable development.
Keywords: 650; corporate social responsibility (CSR); stakeholder influence; corporate reputation; sustainable development